Direct‐Write Formation and Dissolution of Silver Nanofilaments in Ionic Liquid‐Polymer Electrolyte Composites. Issue 39 (17th August 2018) - Chao, Zhongmou; Radka, Brian P.; Xu, Ke; Crouch, Garrison M.; Han, Donghoon; Go, David B.; Bohn, Paul W.; Fullerton‐Shirey, Susan K.
Abstract: Materials with reconfigurable optical properties are candidates for applications such as optical cloaking and wearable sensors. One approach to fabricate these materials is to use external fields to form and dissolve nanoscale conductive channels in well‐defined locations within a polymer. In this study, conductive atomic force microscopy is used to electrochemically form and dissolve nanoscale conductive filaments at spatially distinct points in a polyethylene glycol diacrylate (PEGDA)‐based electrolyte blended with varying amounts of ionic liquid (IL) and silver salt. The fastest filament formation and dissolution times are detected in a PEGDA/IL composite that has the largest modulus (several GPa) and the highest polymer crystal fraction. This is unexpected because filament formation and dissolution events are controlled by ion transport, which is typically faster within amorphous regions where polymer mobility is high. Filament kinetics in primarily amorphous and crystalline regions are measured, and two different mechanisms are observed. The formation time distributions show a power‐law dependence in the crystalline regions, attributable to hopping‐based ion transport, while amorphous regions show a normal distribution. The results indicate that the timescale of filament formation/dissolution is determined by local structure, and suggest that structure could be used to tune the optical properties of the film. Abstract : An electrolyte consisting of a UV‐crosslinkable polymer and an ionic liquid is presented with potential application as an optically reconfigurable metamaterial film. Direct‐write of nanofilaments is demonstrated through the film using conductive atomic force microscopy, showing that filament formation and dissolution kinetics are enhanced within the composition with the largest modulus and the highest polymer crystal fraction.